2016
DOI: 10.1097/jpn.0000000000000153
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Tobacco Smoke Exposure and Congenital Heart Defects

Abstract: Tobacco use and second-hand smoke exposure during pregnancy are linked to a host of deleterious effects on the pregnancy, fetus, and infant. Health outcomes improve when women quit smoking at any time during the pregnancy. However, the developing heart is vulnerable to noxious stimuli in the early weeks of fetal development, a time when many women are not aware of being pregnant. Congenital heart defects are the most common birth defects. Research shows an association between maternal tobacco exposure, both ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Cigarette smoking is perhaps the single most avoidable cause of adverse pregnancy outcomes, increasing the risk for low birth weight, underdeveloped organs, congenital anomalies, preterm birth, fetal mortality, and morbidity (Baba, Wikstrom, Stephansson, & Cnattingius, ; CDC, ; Forest & Priest, ; Harrod, Reynolds, Chasan‐Taber, et al, ; Holbrook, ; Kleinman, Pierre, Madans, et al, ; Mund, Louwen, Klingelhoefer, & Gerber, ; Rogers, ; Rogers, ; Shaw, Carmichael, Vollstet, et al, ). Moreover, maternal smoking during pregnancy has been associated with adverse neurobehavioral, cardiovascular and respiratory consequences in offspring, many of which persist into adulthood (CDC, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is perhaps the single most avoidable cause of adverse pregnancy outcomes, increasing the risk for low birth weight, underdeveloped organs, congenital anomalies, preterm birth, fetal mortality, and morbidity (Baba, Wikstrom, Stephansson, & Cnattingius, ; CDC, ; Forest & Priest, ; Harrod, Reynolds, Chasan‐Taber, et al, ; Holbrook, ; Kleinman, Pierre, Madans, et al, ; Mund, Louwen, Klingelhoefer, & Gerber, ; Rogers, ; Rogers, ; Shaw, Carmichael, Vollstet, et al, ). Moreover, maternal smoking during pregnancy has been associated with adverse neurobehavioral, cardiovascular and respiratory consequences in offspring, many of which persist into adulthood (CDC, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to note that the risk effect of SHS on circulatory system defects was significant (OR = 1.75), consistent with previous studies on congenital heart defects. Forest et al observed a risk association between maternal tobacco exposure (both active and passive) during the periconceptional period and congenital heart defects 28 . Deng et al reported that periconceptional paternal smoking might increase the risk of certain subtypes of congenital heart defects 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Reduced blood mononuclear cells viability from the umbilical cord and an increase in ROS production have been reported in pregnant smokers compared to non-smokers (Rua Ede et al, 2014). Of note is recent evidence supporting the association between maternal tobacco exposure during the periconceptional period and congenital heart defects (Forest and Priest, 2016).…”
Section: Cigarette Smoke Agentsmentioning
confidence: 99%